Corporate and Brand Images and Customer Loyalty - Hadian, Diky; Kusuma, Sunan; Dediwan, Daniati; Margaretha, Yolla (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study aims to investigate three relationships. The first is between company image and customer loyalty (CL). The second is between brand image and CL. The final decision is between a company and the brand image. Moreover, to meet this goal, readers of the West Java Tribun Daily Newspaper in Bandung are employed as the sample. Unfortunately, this study only gathered data from 75 people using the convenience sampling technique. Moreover, it analyzed their responses statistically using confirmatory factor and reliability analyses, as well as assessment model criteria and t-statistics, to examine the shaped hypotheses using a partial least squares-based structural equation model. As a result, three positive tendencies occur: (1) Consumers with a stronger brand image will have better loyalty, (2) the higher their brand image, the higher their loyalty, and (3) the customers with a better company image will have a better brand image. Based on these facts, this study recommends that West Java Tribun News in Bandung pay attention to the digital media content background, such as YouTube and social media. Additionally, its assigned staff members should interact with the readers by replying to their comments on these media.